Comprehensive Physiology 2016
DOI: 10.1002/cphy.c150041
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Skeletal Muscle by microRNAs

Abstract: MicroRNAs (miRNAs) are a class of small noncoding RNAs highly conserved across species. miRNAs regulate gene expression posttranscriptionally by base pairing to complementary sequences mainly in the 3'-untranslated region of their target mRNAs to induce mRNA cleavage and translational repression. Thousands of miRNAs have been identified in human and their function has been linked to the regulation of both physiological and pathological processes. The skeletal muscle is the largest human organ responsible for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 112 publications
2
54
0
1
Order By: Relevance
“…A study on translational repression without RNA destabilization has also been reported (38). In muscle atrophy, the expression levels of miR-30 family were reduced (39), which is consistent with our present study.…”
Section: Discussionsupporting
confidence: 92%
“…A study on translational repression without RNA destabilization has also been reported (38). In muscle atrophy, the expression levels of miR-30 family were reduced (39), which is consistent with our present study.…”
Section: Discussionsupporting
confidence: 92%
“…Subsets of miRNAs can be described as striated muscle‐specific (miR‐1, miR‐133a, miR‐133b, miR‐206, miR‐208a, miR‐208b, and miR‐499) or muscle‐enriched (miR‐486). They are involved in myoblast proliferation/differentiation, muscle regeneration, or fibre‐type specification (for review, refer to Diniz and Wang). The tissue specificity of myomiRs is due either to the genomic location of their coding DNA within introns of myosin heavy chain genes or to transcriptional control by muscle‐specific transcription factors such as MyoD, Mef2, or Srf .…”
Section: Microrna Biogenesis and Myomirsmentioning
confidence: 99%
“…MiRNAs are non-coding RNAs, 19-22 nucleotides long, which act as post-transcriptional regulators of gene expression. The role of miRNAs in the regulation of key biological processes in skeletal muscle is well-established (9) and they serve as diagnostic, prognostic biomarkers, and as molecular outcome measures in various biomedical fields (10,11). Previously, our group used gene network analysis to identify two miRNAs, miR-30c, and miR-181a and validated them as reliable serum diagnostic biomarkers for DMD (12).…”
Section: Introductionmentioning
confidence: 99%